Externalidades, cambio climático y eficiencia energética - Macines Romero, Rogelio (2009)
Climate change is caused by the greenhouse gas effect accumulating in the atmosphere without being absorbed by nature. The United Nations has yearly meetings to discuss this issue remains one of the solutions using renewable resources. Effects that cause by climate change are considered externalities industrialised countries to the countries no industrialised, there is need to find immediate solutions one of which the efficient use of energy.